2014
DOI: 10.3382/ps.2013-03536
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of combined chemical and physical treatments on the reduction of resident microorganisms and Salmonella Typhimurium attached to chicken skin

Abstract: This study was conducted to evaluate the efficacy of sodium hypochlorite (NaOCl, 0-200 mg/kg), thiamine dilauryl sulfate (TDS, 1,000 mg/kg), and ultrasound (37 kHz, 380 W) on reducing Salmonella Typhimurim, mesophilic aerobic bacteria (MAB), and coliforms on chicken skin. Chemical and physical treatments were applied for 5 min either singly or jointly, and Salmonella previously inoculated on chicken skin were quantitatively assessed using brilliant green agar, and the populations of MAB and coliforms in the na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Although chicken is chemically sanitized during processing and subsequently cleaned before packaging, some microorganisms cannot be removed completely, especially bacteria strongly attached to chicken skin [5, 14, 23, 30]. This is because these microorganisms, including Salmonella and Campylobacter, are able to become entrapped in deep skin layers, crevices, or feather follicles, thus becoming protected from chemical agents [5, 15, 29]. …”
mentioning
confidence: 99%
“…Although chicken is chemically sanitized during processing and subsequently cleaned before packaging, some microorganisms cannot be removed completely, especially bacteria strongly attached to chicken skin [5, 14, 23, 30]. This is because these microorganisms, including Salmonella and Campylobacter, are able to become entrapped in deep skin layers, crevices, or feather follicles, thus becoming protected from chemical agents [5, 15, 29]. …”
mentioning
confidence: 99%
“…Immunohistochemistry was effective for identifying specific sites of Salmonella localization and in chicken and turkey skin, Salmonella cells were organized in clusters on the epidermal keratin and were occasionally present in the lumen of feather follicles. Studies of skin that was inoculated with Salmonella have reported bacterial cells present on the flat areas and ridges of the skin, and entrapped in feather follicles (Kim et al, 1996;Lee et al, 2014). This study is the first that describes Salmonella cells within the lumen of feather follicles of colonized poultry.…”
Section: Discussionmentioning
confidence: 73%
“…Unfortunately, Salmonella cells lodged in crevices and within feather follicles are protected from rinses and chemical treatments (Lillard, 1989;Kim et al, 1996;Lee et al, 2014). Similar observations have been made if combination of sonification and chemical treatments is used on poultry carcasses (Lillard, 1993;Lee et al, 2014). Entrapped Salmonella cells can be released once skin is ground and this may contribute to contamination of ground poultry when ground skin is mixed with other ground components.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Heidelberg controls. Sample preparation for electron microscopy was conducted as previously described with some modifications ( Lee et al, 2014 ). Briefly, immediately after each treatment, the skin samples were stored in primary fixative [3% paraformaldehyde, 1.5% glutaraldehyde, and 2.5% sucrose in 0.1 M sodium cacodylate buffer with 5mM calcium chloride and 5mM magnesium chloride (pH 7.4)] for 12 h. Then the samples were fixed in 2% osmium tetroxide and 0.1 M sodium cacodylate buffer for 12 h. Then the samples were washed in ultrapure water (NANOpure Infinity ® ; Barnstead/Thermo Fisher Scientific; Waltham, MD, United States) and dehydrated by ascending grades of ethanol series.…”
Section: Methodsmentioning
confidence: 99%